2016
DOI: 10.1038/nature16481
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the E6/E6AP/p53 complex required for HPV-mediated degradation of p53

Abstract: Summary The p53 pro-apoptotic tumor suppressor is mutated or functionally altered in most cancers. In epithelial tumors induced by “high-risk” mucosal Human Papillomaviruses (hrm-HPVs), including human cervical carcinoma and a growing number of head-and-neck cancers 1, p53 is degraded by the viral oncoprotein E6 2. In this process, E6 binds to a short LxxLL consensus sequence within the cellular ubiquitin ligase E6AP 3. Subsequently, the E6/E6AP heterodimer recruits and degrades p53 4. Neither E6 nor E6AP are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
398
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 389 publications
(414 citation statements)
references
References 40 publications
12
398
0
4
Order By: Relevance
“…However, it has also been identified that low-risk HPV-E6 binds to the C-terminal region of p53, which does not initiate p53 degradation (16). The results of the present study support the latter observation and suggest that low-risk HPV-E6 cannot degrade p53, which may be the primary reason that infection with low-risk HPV does not lead to the development of malignant cancer (17,18). Furthermore, DC exposure to low-risk HPV-6E6 induces apoptosis via the upregulation of apoptosis-associated proteins, including p53, Bax, Bak and cytochrome c. This is supported by the results of a study by Manjarrez et al (19) who demonstrated that p53 levels were higher in papillomatosis than in normal larynxes.…”
Section: Discussionsupporting
confidence: 79%
“…However, it has also been identified that low-risk HPV-E6 binds to the C-terminal region of p53, which does not initiate p53 degradation (16). The results of the present study support the latter observation and suggest that low-risk HPV-E6 cannot degrade p53, which may be the primary reason that infection with low-risk HPV does not lead to the development of malignant cancer (17,18). Furthermore, DC exposure to low-risk HPV-6E6 induces apoptosis via the upregulation of apoptosis-associated proteins, including p53, Bax, Bak and cytochrome c. This is supported by the results of a study by Manjarrez et al (19) who demonstrated that p53 levels were higher in papillomatosis than in normal larynxes.…”
Section: Discussionsupporting
confidence: 79%
“…We found that Arg55 and Arg131 of HPV16 E6, which provide crucial contacts to acidic residues of the LxxLL peptide of E6AP (25), are conserved (at least as positively charged residues) in HPV49 E6, but not in HPV38 E6. Similarly, the key p53-binding residue Asp49 (26) is conserved in HPV49, whereas it becomes an Asn residue in HPV38 E6 ( Supplementary Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we were able to solve the crystal structure of a minimal ternary complex, comprising HPV16 E6, e6ap and the core (or DNA binding) domain of p53 (called p53core from hereon) 6 (Fig. 1, top and middle).…”
mentioning
confidence: 99%